Protein-based micro- and nano-transporters for gut microbiota modulators: advances in delivery strategies and gut health benefits - Rana, Mohammad Nasiruddin; Saifullah, Md.; Saeid, Abu; Kamal, Md. Murtuza; Gao, Xiangjing; Gao, Xiangwei (Frontiers in Bioengineering and Biotechnology, 2025)
Human gut microbiota (GM) is essential for gut health, and its dysbiosis is associated with diseases such as inflammatory bowel disease, obesity, and cancers. Natural GM modulators, including probiotics, bioactive phytochemicals, and peptides, have shown great potential in restoring microbial balance. However, their effectiveness is limited by stability, bioavailability, and targeted delivery to the gut. Protein-based micro- and nano-transporters have recently emerged as innovative platforms capable of overcoming these delivery barriers and improving the therapeutic performance of natural GM modulators. Here, we critically review the design strategies, functional performance, and therapeutic outcomes of various protein-based carriers, including composite hydrogels, stimuli-responsive microgels, targeted nanocomplexes, mucoadhesive microcapsules, and electrospun nanofibers. Furthermore, we discuss how these advanced systems ameliorate gut dysbiosis, modulate immune responses, enhance intestinal barrier integrity, and promote beneficial microbial growth. Finally, current challenges and future perspectives for clinical translation are outlined. Overall, this review aims to provide a mechanistic and practical foundation for the development of next-generation protein-based transporters for microbiota-targeted therapies.